Embodiment and Presence in Virtual Reality After Stroke. A Comparative Study With Healthy Subjects - Borrego, Adrián; Latorre, Jorge; Alcañiz, Mariano; Llorens, Roberto (Frontiers in Neurology, 2019)
The ability of virtual reality (VR) to recreate controlled, immersive, and interactive environments that provide intensive and customized exercises has motivated its therapeutic use after stroke. Interaction and bodily presence in VR-based interventions is usually mediated through virtual selves, which synchronously represent body movements or responses to events on external input devices. Embodied self-representations in the virtual world not only provide an anchor for visuomotor tasks, but their morphologies can have behavioral implications. While research has focused on the underlying subjective mechanisms of exposure to VR on healthy individuals, the transference of these findings to individuals with stroke is not evident and remains unexplored, which could affect the experience and, ultimately, the clinical effectiveness of neurorehabilitation interventions. This study determined and compared the sense of embodiment and presence elicited by a virtual environment under different perspectives and levels of immersion in healthy subjects and individuals with stroke. Forty-six healthy subjects and 32 individuals with stroke embodied a gender-matched neutral avatar in a virtual environment that was displayed in first-person perspective with a head-mounted display and in third-person perspective with a screen, and were asked to interact in a virtual task for 10 minutes under each condition in counterbalanced order, and complete two questionnaires about the sense of embodiment and presence experienced during the interaction. The sense of body-ownership, self-location, and presence were more vividly experienced in first-person than in third-person perspective by both healthy subjects (p<.001, ƞ2p=.212; p=.005, ƞ2p=.101; p=.001, ƞ2p=.401, respectively) and individuals with stroke (p<.019, ƞ2p=.070; p=.001, ƞ2p=.135; p=.014, ƞ2p=.077, respectively). In contrast, no perspective-related differences were found for agency in any group. All measures were consistently higher for healthy controls than for individuals with stroke, but differences between groups only reached statistical significance in presence under the first-person condition (p<.010, ƞ2p=.084). In spite of these differences, the participants experienced a vivid sense of embodiment and presence in almost all conditions. These results provide first evidence that, although less intensively, embodiment and presence are similarly experienced after stroke as in healthy individuals, which could support the vividness of their experience and, consequently, the effectiveness of VR-based interventions.